2018
DOI: 10.1172/jci96791
|View full text |Cite
|
Sign up to set email alerts
|

Self-adjuvanting nanoemulsion targeting dendritic cell receptor Clec9A enables antigen-specific immunotherapy

Abstract: could be achieved, the immunogenicity of TNE-encapsulated antigen was not explored. Here we show unexpectedly, given the lack of DC activation by anti-Clec9A-antigen conjugates, that in the absence of adjuvant, cross-presenting DCs targeted with antigenClec9A-TNE stimulate DC activation, antigen-specific CTLs, and highly effective tumor-specific immunity, dependent on the presence of CD4 helper epitopes and CD40 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 62 publications
3
60
0
Order By: Relevance
“…Hence, an improved understanding of the disease mechanisms will enable the development of more efficient nanomedicines with mechanisms of action beyond tumor nanoparticle accumulation [19,20]. For instance, nanoparticles are currently being explored in the fields of adoptive cell therapy and immune modulation in various stages of preclinical and clinical development [21]. Moreover, recent preclinical studies and clinical trials have shown benefits of combination therapies, and particularly, the ability of nanoparticles to simultaneously deliver therapeutic agents, such as small molecules, genetic material, and biologics [22].…”
mentioning
confidence: 99%
“…Hence, an improved understanding of the disease mechanisms will enable the development of more efficient nanomedicines with mechanisms of action beyond tumor nanoparticle accumulation [19,20]. For instance, nanoparticles are currently being explored in the fields of adoptive cell therapy and immune modulation in various stages of preclinical and clinical development [21]. Moreover, recent preclinical studies and clinical trials have shown benefits of combination therapies, and particularly, the ability of nanoparticles to simultaneously deliver therapeutic agents, such as small molecules, genetic material, and biologics [22].…”
mentioning
confidence: 99%
“…Recent preclinical studies and clinical trials combined the use of DC stimulators with the growth factor FMS-like tyrosine kinase-3 ligand (FLT3L) to increase DC numbers in peripheral blood [59,60]. For optimal delivery, the adjuvants can be encapsulated in nanoparticles, liposomes, or immunostimulatory complexes specifically targeting DCs [61][62][63], whereas to guarantee a sufficient availability of immunogenic TAAs, in situ vaccination can be combined with ICD-inducing therapeutic modalities, such as doxorubicine or radiotherapy.…”
Section: In Situ Vaccinationmentioning
confidence: 99%
“…Alternatively, specific peptides selected by in vitro evolution systems and beads coated with a synthetic F-actin/myosin II complex can be used for in vivo targeting of antigens toward DNGR-1 (23,24). Moreover, anti-DNGR-1 antibodies can be used to deliver antigen-containing nanoemulsions with immunostimulatory properties (25). Upon engagement with F-actin or monoclonal antibodies, surface DNGR-1 is internalized (10) and directed to non-degradative endosomal compartments (8), which are associated with enhanced antigen cross-presentation (26).…”
Section: Dngr-1 As a Targetable Cdc1 Markermentioning
confidence: 99%